3x + 2y = -8

y = x + 1

For the substitution method, you substitute one variable for the other. In this case, we're given that y = x +1.

So we can substitute x+1 in for every y we see in the first equation:

3x + 2(x+1) = -8

Distribute the 2 across the x+1:

3x + 2x + 2 = -8

Combine like terms:

(3+2)x + 2 = -8

5x + 2 = -8

Subtract 2 from both sides:

5x = -10

Divide both sides by 5:

x = -2.

Now substitute x = -2 into either one of your equations to get y:

y = x+1

y = -2+1 = -1

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up